KARAKTER SOSIAL (POLA PIKIR, POLA SIKAP, DAN POLA TINDAK) SISWA MI/SD PADA GENERASI ALPHA DAN BETA - Suci Khoirani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Generational shifts have had a significant impact on the development of students' social character at the Madrasah Ibtidaiyah (MI) and Elementary School (SD) levels. This article aims to analyze the social character of MI/SD students in Generation Alpha (born 2010–2024) and Generation Beta (born 2025–present) which includes mindsets, attitudes, and behavior patterns. The method used is a narrative literature review and trend analysis based on scientific publications, policy reports, and child development studies for the period 2021–2026. The results show that Generation Alpha students tend to have a visual-digital mindset, a collaborative attitude but are vulnerable to cognitive distractions, and a participatory behavior pattern but require strengthening digital ethics and emotional resilience. Meanwhile, the analysis of Generation Beta is projective because this group has just entered its early years, but early trends indicate a more intuitive mindset towards artificial intelligence, a more emotionally stable attitude, and behavior patterns that require media literacy assistance and social value familiarization from an early age. The discussion emphasizes the need for an adaptive educational approach, the integration of Pancasila values ​​and Islamic morals, and structured school-family collaboration. This article provides strategic recommendations for educators and policymakers in designing social character strengthening programs that are responsive to generational dynamics without neglecting moral and religious foundations. ABSTRAK Pergeseran generasi membawa dampak signifikan terhadap perkembangan karakter sosial siswa di tingkat Madrasah Ibtidaiyah (MI) dan Sekolah Dasar (SD). Artikel ini bertujuan untuk menganalisis karakter sosial siswa MI/SD pada Generasi Alpha (lahir 2010–2024) dan Generasi Beta (lahir 2025–sekarang) yang mencakup pola pikir, pola sikap, dan pola tindak. Metode yang digunakan adalah tinjauan literatur naratif dan analisis tren berbasis publikasi ilmiah, laporan kebijakan, serta kajian perkembangan anak periode 2021–2026. Hasil menunjukkan bahwa siswa Generasi Alpha cenderung memiliki pola pikir visual-digital, sikap kolaboratif namun rentan terhadap distraksi kognitif, serta pola tindak yang partisipatif namun memerlukan penguatan etika digital dan resiliensi emosional. Sementara itu, analisis terhadap Generasi Beta bersifat proyektif karena kelompok ini baru memasuki usia dini, namun tren awal mengindikasikan pola pikir yang lebih intuitif terhadap kecerdasan buatan, sikap yang lebih stabil secara emosional, dan pola tindak yang memerlukan pendampingan literasi media serta pembiasaan nilai sosial sejak dini. Pembahasan menekankan perlunya pendekatan pendidikan yang adaptif, integrasi nilai Pancasila dan akhlak Islami, serta kolaborasi sekolah-keluarga yang terstruktur. Artikel ini memberikan rekomendasi strategis bagi pendidik dan pembuat kebijakan dalam merancang penguatan karakter sosial yang responsif terhadap dinamika generasi tanpa mengabaikan fondasi moral dan keagamaan